2016
DOI: 10.5625/lar.2016.32.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary effects of thiopental versus propofol as an induction agent prior to isoflurane anesthesia in chair trained rhesus macaques (Macaca mulatta)

Abstract: The purpose of this study was to evaluate the effects of thiopental versus propofol on cardiopulmonary functions, when used as an induction agent prior to isoflurane anesthesia in rhesus monkeys. Eight healthy rhesus monkeys weighing 3.72 to 5.7 kg, 4-5 years old, were used in the study. Anesthesia was induced with thiopental or propofol intravenous injection, and then maintained with isoflurane in oxygen for 45 minutes. Cardiopulmonary measurements were obtained before and 5, 15, 30, 45, and 60 minutes after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Choi et al . [ 44 ] also compared the cardiopulmonary effects of sodium thiopental and propofol. They found that propofol causes fewer hemodynamic changes as compared to sodium thiopental, including a decrease in systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al . [ 44 ] also compared the cardiopulmonary effects of sodium thiopental and propofol. They found that propofol causes fewer hemodynamic changes as compared to sodium thiopental, including a decrease in systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%